2007
DOI: 10.1021/la701936x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Nonmotile Pseudomonas aeruginosa on “Soft” Polyelectrolyte Layer in a Radial Stagnation Point Flow System:  Measurements and Model Predictions

Abstract: Prediction of bacterial deposition rates onto substrates in natural aquatic systems is quite challenging because of the inherent complexity of such systems. In this study, we compare experimental deposition kinetics of nonmotile bacteria (Pseudomonas aeruginosa) on an alginate-coated substrate in a radial stagnation point flow (RSPF) system to predictions based on DLVO theory. The "softness" of the surface layer of the bacteria and alginate-coated substrate was considered in the calculations of their electroki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 49 publications
8
62
0
Order By: Relevance
“…The total number of adsorption and 4. Example of the distance-dependent free energy of interaction between S. epidermidis ATCC 35983 and hydrophilic glass and hydrophobic DDS-coated glass, using the extended DLVO-theory and surface characteristics as reported previously [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of adsorption and 4. Example of the distance-dependent free energy of interaction between S. epidermidis ATCC 35983 and hydrophilic glass and hydrophobic DDS-coated glass, using the extended DLVO-theory and surface characteristics as reported previously [21].…”
Section: Discussionmentioning
confidence: 99%
“…adhesion in the absence of specific ligand-receptor bonding, than it is on the number of actually adhering bacteria. Interestingly, using a similar experimental set-up and analysis, De Kerchove et al [21] showed that sliding of carboxylated latex particles was virtually absent on hydrophilic quartz but present when an alginate conditioning film was used. It was stated that the properties of the alginate (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the method that employed in previous works to adsorb a layer of PLL onto the silica surface [39,40], which was also provided in the Supplementary Information. Corresponding deposition experiments on PLL-coated silica surfaces were performed over the same ionic strength range in both NaCl and CaCl 2 solutions with the same EPS influent concentration as that conducted on bare silica surfaces.…”
Section: Eps Deposition Experimentsmentioning
confidence: 99%
“…These studies suggest that the retention and transport of pathogens are strongly affected by physical and chemical characteristics of water, such as ionic strength, pH, composition, and physical properties of porous media. Adhesion of pathogenic bacteria and protozoa onto different solid surfaces, such as haematite, silica, and alginate, has also been extensively studied [17][18][19][20][21][22][23]. As demonstrated in the studies focusing on bacteria and protozoa, the composition of electrolyte solution, surface properties, and background macromolecules in the solution are the main factors that govern the adhesion kinetics of bacteria and protozoa.…”
Section: Introductionmentioning
confidence: 99%